PENGEMBANGAN MEDIA PEMBELAJARAN POP UP BOOK PADA MATA PELAJARAN MATEMATIKA SISWA KELAS II SDN CANGKUDU 03 KABUPATEN TANGERANG - Ria Rosita; Een Unaenah; Dilla Fadhillah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is based on mathematics learning on spatial geometry, teachers still use makeshift learning media. The research was conducted to produce Pop Up Book media for spatial geometry mathematics in class II. The main objective of this research is to determine the validity and effectiveness of a Pop Up Book learning media for mathematics on spatial geometry for class II SDN Cangkudu 03 Tangerang Regency. This research uses the Research and Development (R&D) method using the ADDIE model which consists of five stages: (Analysis, Design, Development, Implementation, and Evaluation). Data collection techniques used are observation, interviews, and questionnaires. Quantitative and qualitative data are analyzed using a Likert Scale with an assessment score of 1-5. The results of this research and development show that according to material experts, the validity level is 89.3% of the